Kerjasama pemerintah-badan usaha di Indonesia: Solusi dan celah korupsi - Diaz Adiasma; Didik Mulyanto; Fitriani Nurza; Hilda Alatas (Komisi Pemberantasan Korupsi, 2023)
We need to better understand Public-Private Partnership (PPP), since most people perceive PPP as a riskless solution for government, as it involves private sector funding. In Indonesia, infrastructure development is one of the top priority sectors for Joko Widodo’s administration, and PPP has become a viable option due to budgetary constraints. However, PPP is not an impeccable solution, as there are weaknesses and loopholes for corruption to be aware of. In this literature review, we combine our previous study on Indonesia’s toll road PPP with other PPP studies to identify the weaknesses and corruption loopholes in PPP practices in Indonesia. There is clear evidence that PPP projects could end up as “white elephants”, indicating misallocation of resources and poor planning. PPP could also be used to create “fiscal illusion” to deceive public by the government. We also discovered that toll road PPP contracts in Indonesia remain vulnerable, potentially creating room for loopholes and corruption.